MIRZO BOBUR’S ILLNESS - Sobirov Jamshidbek Zokirjon Ogli (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses two types of scholars’ views on the death of Zahiruddin Muhammad Babur: Humayun’s illness was attributed to Allah and then his condition worsened, and Princess Bayda died of chronic liver failure due to poisoning of Babur.